2003
DOI: 10.1111/1532-7795.1301004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Control and Autonomy Granting: Opposite Ends of a Continuum or Distinct Constructs?

Abstract: This article explores the relationship between parental psychological control and parental autonomy granting, and the relations between these constructs and indicators of adolescent psychosocial functioning, in a sample of 9,564 adolescents from grades 9 to 12. Participants completed a comprehensive parenting questionnaire as well as several measures of psychosocial adjustment. Confirmatory factor analyses of the parenting items revealed discrete factors for psychological control and autonomy granting, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
326
5
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(381 citation statements)
references
References 38 publications
26
326
5
14
Order By: Relevance
“…Thus, in this scale a high score in one style implies automatically a weak score on the other one. However, previous work (e.g., Barber, 1996;Grolnick, 2003;Silk et al, 2003) has shown that autonomy support and control are two independent dimensions. Our results corroborate these findings by showing that providing greater autonomy support will not inevitably decrease a controlling style.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, in this scale a high score in one style implies automatically a weak score on the other one. However, previous work (e.g., Barber, 1996;Grolnick, 2003;Silk et al, 2003) has shown that autonomy support and control are two independent dimensions. Our results corroborate these findings by showing that providing greater autonomy support will not inevitably decrease a controlling style.…”
Section: Discussionmentioning
confidence: 95%
“…For example, in a study dealing with the relationships between parental psychological control, parental autonomy granting and indicators of adolescents' psychosocial functioning, Silk et al (2003) suggested that psychological control is more than the absence of autonomy granting. In other words, the absence of autonomy-support could be displayed via a "neutral" style which does not reflect the will to control people.…”
mentioning
confidence: 99%
“…Conversely, behaviors undermining autonomy and relatedness during interactions with mothers are linked to increases in depression during early adolescence . The self -report literature examining effects of parenting reveal a similar pattern: Adolescents ' reports of psychological control versus autonomy support are cross -sectionally linked (in expected directions) to reports of self -concept, self -worth, and well -being (Aquilino & Supple, 2001 ;Frank et al, 2002 ;Laible & Carlo, 2004 ;Silk, Morris, & Kanaya, 2003 ;Soenens et al, 2007 ). Given the links between parental autonomy support versus undermining and views of the self, it is perhaps not surprising that these constructs are also linked to psychological functioning, particularly with regard to internalizing symptoms.…”
Section: Autonomy Processes Views Of the Self And Internalizing Promentioning
confidence: 89%
“…Petit et al). Conversely, self -report studies have indicated that parents ' granting of psychological autonomy is linked with a range of positive emotional and behavioral outcomes, including less depressed affect and fewer externalizing problems both concurrently and longitudinally (Barber & Olson, 1997 ;Eccles, Early, Frasier, Belansky, & McCarthy, 1997 ;Herman, Dornbusch, Herron, & Herting, 1997 ;Silk et al, 2003 ). Similarly, observations of behavior promoting of cognitive/verbal autonomy while also maintaining relatedness during a family discussion have been linked to lower levels of adolescent depression over time, as rated by observers during a clinical interview (Allen et al, 1994a ).…”
Section: Autonomy Processes Views Of the Self And Internalizing Promentioning
confidence: 99%
“…For the other two dimensions evaluated--behavioral control and the promotion of autonomy--these made no significant contributions. This is probably due to the fact that although they are important components of the parenting style, their positive effects on adolescent development are reflected in other aspects, such as behavioral adjustment or academic performance (Silk, Morris, Kanaya, and Steinberg, 2003). At the same time, the lack of a relationship between the promotion of autonomy and internalizing problems may be a cultural confound.…”
Section: Discussionmentioning
confidence: 99%